Excitation of the hyperfine levels of 13CN and C15N in collisions with H2 at low temperatures. Issue 2 (21st November 2014) - Flower, D. R.; Lique, F.
Abstract : Cross-sections and rate coefficients for transitions between the fine and hyperfine levels of the isotopologues, 13 CN, and C 15 N, of the CN radical, induced by collisions with para-H2 in its rotational ground state, j = 0, have been computed. The effects of the isotopic shift of the centre of mass on the interaction potential were included, and energy levels specific to each isotopologue were used. The isotopologue-dependence of the results was found to be such that we recommend that rate coefficients specific to each isotopologue should be used when analysing observations of hyperfine transitions. The numerical values of the rate coefficients are available for kinetic temperatures T ≲ 10 2  K.